2011
DOI: 10.1007/s10165-011-0544-2
|View full text |Cite
|
Sign up to set email alerts
|

Smoking is associated with an increased risk of developing ACPA-positive but not ACPA-negative rheumatoid arthritis in Asian populations: evidence from the Malaysian MyEIRA case–control study

Abstract: We investigated the association between cigarette smoking and the risk of developing rheumatoid arthritis (RA) in the Malaysian population. A total of 1,056 RA patients and 1,416 matched controls aged 18-70 years within a defined area of Peninsular Malaysia were evaluated in a case-control study between August 2005 and December 2009. A case was defined as a person with early diagnosed RA using the 1987 American College of Rheumatology criteria for RA. Controls were randomly selected matched for sex, age, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
1
15
0
1
Order By: Relevance
“…A relation between pack years and the risk of ACPA-positive RA was also seen, with an OR of 3.3 for <20 pack years and an OR of 5.2 for at least 20 pack years. 29 This is in contrast to the Japanese population-based study, where only a significant association between the amount of smoking and high levels of ACPA was found. 20 Finally, joint complaints were found to be an independent risk factor for ACPA positivity, even with the limited joint complaint questions that were asked to the participants.…”
Section: Discussionmentioning
confidence: 64%
“…A relation between pack years and the risk of ACPA-positive RA was also seen, with an OR of 3.3 for <20 pack years and an OR of 5.2 for at least 20 pack years. 29 This is in contrast to the Japanese population-based study, where only a significant association between the amount of smoking and high levels of ACPA was found. 20 Finally, joint complaints were found to be an independent risk factor for ACPA positivity, even with the limited joint complaint questions that were asked to the participants.…”
Section: Discussionmentioning
confidence: 64%
“…While smoking is clearly associated with seropositive RA, this association is attenuated or null for seronegative RA [17 28 30]. Some studies suggest that seronegative RA may be a heterogeneous collection of diseases without a common pathogenesis or distinct risk factors [31].…”
Section: Cigarette Smoking Cessation and Overall Risk For Seropositmentioning
confidence: 99%
“…Furthermore, our group also demonstrated that smoking is associated with RA development and that this effect is restricted to the ACPA-positive RA subset [16]. However, the question whether the HLA-DRB1 SE alleles and smoking interacts in providing an increased risks for ACPA-positive RA remains to be answered in our non-Caucasian population.…”
Section: Introductionmentioning
confidence: 99%